Traditional Use of Medicinal Plants in South-Eastern Serbia (Pčinja District): Ethnopharmacological Investigation on the Current Status and Comparison With Half a Century Old Data - Živković, Jelena; Ilić, Milan; Šavikin, Katarina; Zdunić, Gordana; Ilić, Aleksandra; Stojković, Dejan (Frontiers in Pharmacology, 2020)
Balkan Peninsula is one of the most important biodiversity centers in Europe. Despite that, the usage of plant species in the traditional medicine of some Balkan regions remained largely unexplored in the past. This study aimed to collect and document data on the traditional use of medicinal plants in Pčinja district in South-Eastern Serbia, which is among the least developed regions in Serbia. Also, comparison with data collected by Dr. Jovan Tucakov, in a book called Herbal therapy was conducted. The survey was carried out using semi-structured interviews and 113 informants were interviewed. Quantitative ethnobotany factors were calculated, allowing us discussing the results. The informants reported data on 86 medicinal plants belonging to 43 families in Pčinja district. Lamiaceae, Asteraceae and Rosaceae were the dominant locally used families. The species with the highest number of use reports were Mentha piperita, Matricaria chamomilla and Hypericum perforatum. Gastrointestinal ailments, respiratory problems and skin diseases were the most frequently reported indications. Usually, the administration was primarily oral followed by topical applications. Leaves were dominantly exploited plant parts and the most frequent preparation form was infusion. Medicinal plants in Pčinja district are mainly used as a mode of primary health care for treating minor health issues. After comparing our results with the ones collected half a century ago by Dr. Jovan Tucakov we can conclude that plant species mentioned in our investigation previously had a much wider spectrum of application.